Kinerja Unit Pelaksana Teknis Museum Negeri Provinsi Sumatera Utara Dalam Meningkatkan Jumlah Pengunjung di Medan - Annisa Sanny; Yudi Kurniawan; Tunggul Sihombing (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This study aims to determine and describe how the Performance of the Technical Implementation Unit of the State Museum of North Sumatra Province in Increasing the Number of Museum Visitors in Medan.The method used in this research is descriptive qualitative, with an approach using the indicators proposed by Dwiyanto Agus, namely Productivity, Service Quality, Responsiveness and Accountability as indicators to find out what the results of employee performance are.The results showed that the employee's performance in increasing the number of museum visitors at the Technical Implementation Unit of the State Museum of North Sumatra Province was still optimal, because it had made performance improvements in terms of time, cost as well as processes and procedures. This can be seen from the quality of service provided by the museum to visitors who can provide satisfaction.